Techniques adopted by teaching staf at Duhok University - Armia, Remonda I.; Ismail, Adham I.K. (Humanities Journal of University of Zakho, 2016)
The research aims to identify the styles of encountering psychological stresses of Duhok University lecturers and if there were difference in style of encountering stresses for samples research according to the gender, specialize, the social state and scientific title. The sample of the research consisted of (188) lecturers, (106) of them are males and (82) of them females they have been chosen in a randomly way. To achieve research aims specific tools are prepared from (30) items contributed on three styles they are the style of escaping and withdrew the style of the positive and negative confrontation. It has been verified validity and reliability of the instrument, to extract the results were used T-test of one sample and the T-test of two independent samples and one way Anova. The results were the sample of the research used style of positive confrontation, there are no different between variable gender, social state and scientific title in the face of the three styles of psychological stresses, while the results for the variable specialization showed difference statistically significant in favor of humanitarian specialization in the style of positive confrontation.